1995
DOI: 10.1029/94jb03217
|View full text |Cite
|
Sign up to set email alerts
|

Relation of peralkaline magmatism to heterogeneous extension during the middle Miocene, southeastern Nevada

Abstract: Volcanism migrated southward in the northern Basin and Range province in the Oligocene and early Miocene to produce voluminous calcalkaline silicic ash flow tuffs. Alkaline volcanism became dominant by middle Miocene (17–14 Ma) as smaller volumes of rhyolite‐trachyte‐basalt suites were erupted from the relatively small Kane Springs Wash caldera complex including the Narrow Canyon, Boulder Canyon, and Kane Springs Wash calderas in southeastern Nevada. Only minor extension affected the Kane Wash area before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…When compared with other large rhyolite provinces (Fig. 5b), e.g., the northern Basin and Range, W United States (Scott et al, 1995), the Yellowstone Plateau, Idaho (Bindeman and Valley, 2001), and the Taupo Volcanic Zone (Brown et al, 1998;Sutton et al, 2000), no any rhyolites from these provinces possess such high peraluminosity comparable with the SP rhyolites in the SCMB. Even the well-known SP rocks, such as Himalaya leucogranites (including Manaslu) (Vidal et al, 1982;Searle et al, 1997;Guillot and Le Fort, 1995), the peraluminosity is far less than these SP rhyolites.…”
Section: Compositions Of A-type Granites Versus Sp and P-mp Rhyolitesmentioning
confidence: 88%
See 1 more Smart Citation
“…When compared with other large rhyolite provinces (Fig. 5b), e.g., the northern Basin and Range, W United States (Scott et al, 1995), the Yellowstone Plateau, Idaho (Bindeman and Valley, 2001), and the Taupo Volcanic Zone (Brown et al, 1998;Sutton et al, 2000), no any rhyolites from these provinces possess such high peraluminosity comparable with the SP rhyolites in the SCMB. Even the well-known SP rocks, such as Himalaya leucogranites (including Manaslu) (Vidal et al, 1982;Searle et al, 1997;Guillot and Le Fort, 1995), the peraluminosity is far less than these SP rhyolites.…”
Section: Compositions Of A-type Granites Versus Sp and P-mp Rhyolitesmentioning
confidence: 88%
“…(b) Other rhyolites from silicic large igneous provinces (SLIPs) and typical SP rocks. (1 and 2) northern Basin and Range rhyolites (Scott et al, 1995); (3) Low-d 18 O Yellowstone rhyolites (Bindeman and Valley, 2001); (4 and 5) the Oruanui rhyolites (Sutton et al, 2000) and Whakamaru ignimbrites (Brown et al, 1998) in the Taupo Volcanic Zone; and (6) representative SP rocks of leucogranites in Himalaya (Searle et al, 1997) in which the black dots are the averaged Manaslu leucogranites of various types (Vidal et al, 1982;Guillot and Le Fort, 1995). Shaded areas are same as in (a).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most extensively studied regions of continental extension is the Basin and Range (B&R) province, where recent work has focused on structure of the upper mantle [Humphreys andDueker, 1994a, 1994b;Zandt et al, 1995;Jones and Phinney, 1998;Wernicke, 1992;Jones et al, 1992;Savage and Sheehan, 2000;Humphreys, 1995;Humphreys et al, 2000;Lowry et al, 2000]. It is generally accepted that the lithosphere has been thinned during the past 15 Myr and that Cenozoic volcanism is related to extension [e.g., Wernicke, 1992;Wernicke et al, 1988;Gans and Bohrson, 1998;Best and Christiansen, 1991;Scott et al, 1995;Jones, 1987;Hawkesworth et al, 1995;Zandt et al, 1995;Walker and Coleman, 1991;Walker et al, 1995]. Despite the general association between extension and volcanism, it has been difficult to constrain the depth and extent of mantle melting that leads to B&R basaltic magmatism.…”
Section: Introductionmentioning
confidence: 99%
“…7C). Strain rates along most of this trend are unknown, but at the southern terminus of the region (at Kane Springs Wash), Scott et al (1995) found that the time of peak extension rate, at 15-13.5 Ma, coincided with the eruption of peralkaline (i.e, high K-index) rocks at 14.4 Ma. These spacetime coincidences indicate that K-index may be a powerful tool for gauging the timing of extensional faulting where stratigraphic or structural information is insuffi cient.…”
Section: Volcanism As Controlled By Crustal Extensionmentioning
confidence: 95%